Recurrent Isolated Oculomotor Nerve Palsy after Radiation of a Mesencephalic Metastasis. Case Report and Mini Review - Grabau, Olga; Leonhardi, Jochen; Reimers, Carl D. (Frontiers in Neurology, 2014)
Introduction: Recurrent oculomotor nerve palsies are extremely rare clinical conditions. Case report: Here, we report on a unique case of a short-lasting recurrent unilateral incomplete external and complete internal oculomotor nerve palsy. The episodic palsies were probably caused by an ipsilateral mesencephalic metastasis of a breast carcinoma and occurred after successful brain radiation therapy. Discussion: While the pathogenic mechanism remains unclear, the recurrent sudden onset and disappearance of the palsies and their decreasing frequency after antiepileptic treatment suggest the occurrence of epilepsy-like brainstem seizures. A review of case reports of spontaneous reversible oculomotor nerve palsies is presented.